Miniaturized Broadside-Coupled Split Ring Resonator Filter For Compact Wireless Applications - Peh, Tee Howe (2017)
The current microwave technology state of the art has been focused on the miniaturization of resonator. The importance of resonator miniaturization is based on the need to implement high frequency circuits in a compact form factor. A novel version of broadside-coupled split ring resonator (BC-SRR) is explored in this thesis by using a method of enhancing the resonators’ capacitance by loading a surface mount capacitor on each individual rings that leads to reduction of resonant frequencies. A miniaturized BC-SRR filter with center frequency of 1 GHz is realized and achieved a miniaturization of 27.17 % by using 0.7 pF surface mount capacitors as compared to a filter that does not use a capacitor. The filter also exhibits a narrowband passband transmission response of 1.65 % fractional band width and excellent upper stopband rejection up to 5.1f0. A novel method to excite the resonator is explored by using advanced transmission line design technique that incorporates multi-layer interaction. Ten samples of capacitor-loaded BC-SRR filter is developed, measured and analyzed in terms of variation and shows excellent tolerance performance with 0.52 % frequency offset from initial design. A single sample is subjected to extreme cold and hot temperatures and show excellent thermal coefficient property with as much as 0.6 MHz passband response shift at both temperature extremes. Finally, the feasibility of using capacitors to further miniaturize broadside-coupled split ring resonator (BCSRR) filter is discussed and recommendations of implementation is proposed and presented.